De facto anonymised microdata file on income tax statistics 1998 - Joachim Merz; Daniel Vorgrimler; Markus Zwick (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2006)
With the data of the de facto anonymised income tax statistics 1998 (FAST 98), the German official statistics are for the first time publishing microdata from the field of fiscal statistics. The scientific community can use these data to analyse politically-relevant questions on the fiscal and transfer system at their own workplace, subject to the premises of article 16 subsec-tion 6 of the Law on Statistics for Federal Purposes, on the basis of real assessment data. Passing on individual data to the scientific community is only possible in a de facto anonymised form. This form may impair possibilities for scientific analysis possibilities. So that anonymised data can nevertheless be used by the scientific community, anonymisation must meet two equal challenges: It must firstly guarantee adequate protection of the individual items of data, and secondly it must optimally conserve the possibilities for analysis of the anonymised data. In order to achieve the right balance between these two goals, the Statistical Offices have involved potential scientific users in the anonymisation work in a research project. In the article entitled De facto anonymised microdata file on income tax statistics 1998, in addition to the anonymisation concept the framework conditions of the project are explained and the analysis possibilities of income tax statistics demonstrated. – – Mit den Daten der anonymisierten Einkommensteuerstatistik von 1998 (FAST 98), veröffentlicht das Statistische Bundesamt Deutschland zum ersten Mal Mikrodaten aus dem Bereich der Finanzstatistik. Die Wissenschaft kann diese Daten nutzen, um politisch relevante Fragen zu Finanz- und Transfersystemen auf der Grundlage echter Bemessungsdaten, unter der Vorraussetzung des 16 Abschnitt 6 des Bundesstatistikgesetzes, zu bearbeiten. Individuelle Daten dürfen nur in faktisch anonymisierter Form an die Wissenschaft weitergegeben werden. Diese Form kann die Möglichkeiten für statistische Analysen einschränken. Damit die anonymisierten Daten dennoch von der Wissenschaft genutzt werden können, stellen sich zwei gleichwertige Herausforderungen an die Anonymisierung: Einerseits muss ein angemessener Schutz für die individuellen Daten sichergestellt werden, andererseits sollten die Möglichkeiten der Analyse anonymisierter Daten weitestgehend erhalten bleiben. Um das richtige Gleichgewicht zwischen diesen beiden Zielen zu finden, hat das Statistische Bundesamt potentielle wissenschaftliche Nutzer in den Prozess der Anonymisierung innerhalb eines Forschungsprojekts mit eingebunden. Der Artikel Die faktisch anonymisierte Mikrodatendatei für die Einkommenssteuerstatistik von 1998 erklärt neben dem Anonymisierungskonzept die Rahmenbedingungen des Projekts und veranschaulicht die Analysemöglichkeiten der Einkommensteuerstatistik.
Keywords: C81; H24; 330; microdata; de facto anonymization; income tax statistic; Mikrodaten; De facto Anonymisierung; Einkommenssteuerstatistik; Einkommensteuer; Statistik; Mikrodaten; Deutschland